SOCIAL SCIENCE OF PUBLIC ADMINISTRATION: AN APPROACH TO THE LEGAL IMPLICATIONS OF HIRING WITHOUT TENDERING - Ribeiro Nunes, Antônio José (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2022)
From the Federal Constitution of 1988, the investiture in public employment goes through approval in a public contest and this prediction, in addition to moralizing, requires planning by the Public Administration In this perspective, the problem of the study presents the question: What are the administrative consequences for the investiture in public positions without public tender? This article aimed to identify the legal implications for the public administration of contracting without tender. It was intended to analyze issues such as nepotism and clientelism, cultural heritage of public administration; to situate the questions related to the constitutional precepts of hiring public servants. The presuppositions of the study point out that the hiring of civil servants has as a precept the realization of a public tender, foreseen as regulatory principles of morality and legality. In order to respond to the objectives of the study and the identified problem, a bibliographic research was carried out based on the theoretical foundations of authors. The results showed the legal implications of hiring without a public tender, showing that the constitutional precepts provide for the realization of a public tender, based on the right of competition and opportunity for At this juncture, the practice of nepotism, legacy of the old public administration, undergoes transformations, being submitted to the framework of administrative improbity to offenders, still under the risk of nullity of the act, fine and loss of position. The Federal Constitution determined meritocracy through a public contest to avoid serving interests outside the public service.